Measurement-based evaluation of the effect of an over-track-exhaust ventilation system on the particulate matter concentration and size distribution in a subway. (March 2021) - Zhao, Qian; Xiao, Yimin; Lin, Jianquan; Mao, Hongzhi; Zeng, Zhen; Liu, Yanan
Highlights: PM under three OTE conditions in TVS and TNVS are both measured. The removal efficiencies of coarse particles is higher when OTE is operating. Whether OTE system is beneficial to tunnel and station depends on the ambient. PM concentration in the tunnel and station is greatly affected by the ambient. PM concentration record 24 h in tunnel and 15 h in station per day. Abstract: To reveal the influence of an over-track-exhaust (OTE) system on particulate matter (PM) concentration and size distribution in underground stations, field measurements were performed at a subway station both in the tunnel ventilation and non-ventilation seasons. By regulating the operating conditions of the OTE system and analyzing different particle size ranges, the characteristics of PM concentration and particulate size distribution under different OTE conditions were obtained. The results show that the normal operation of the OTE system slightly reduces PM concentration, but the effect is negligible. However, it was found that PM concentration increases under long-time operation of the OTE system if the ambient air quality is poor. When the OTE system is operating, the removal efficiencies of particles larger than 2.5 μm are relatively higher. However, the proportion of fine particles (2.5 ) increases because more fine particles enter the station owing to negative pressure. Correlation analyses of different zones also showed the same result and identified the PM source for each zone. Moreover, the variation trends of the daily average concentration of PM in each zone are in accordance with the ambient environment; thus, the external environment may have a strong influence on subway air quality.